2001
DOI: 10.1111/j.1469-7793.2001.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the renin‐angiotensin system on cerebral perfusion following subarachnoid haemorrhage in the rat

Abstract: Subarachnoid haemorrhage (SAH) is a serious condition characterized by a high level of morbidity and mortality. Indeed, some studies have documented the mortality to be as high as 45 % in the 30 days following the trauma (Broderick et al. 1994). Despite improved microsurgical techniques this high level of mortality remains, largely as a consequence of rebleeding, but also due to the development of cerebral vasospasm and/or hydrocephalus resulting in delayed cerebral ischaemia. Indeed, it has been reported that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…Rather, functional but hitherto unknown polymorphism(s) in the candidate region of the gene are in strong linkage disequilibrium with the I/D polymorphism. 33 In experimental animals, ACE inhibitors ameliorated intracerebral vasospasms. 13 Risk of Alzheimer disease repeatedly has been found to be associated with the I allele.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, functional but hitherto unknown polymorphism(s) in the candidate region of the gene are in strong linkage disequilibrium with the I/D polymorphism. 33 In experimental animals, ACE inhibitors ameliorated intracerebral vasospasms. 13 Risk of Alzheimer disease repeatedly has been found to be associated with the I allele.…”
Section: Discussionmentioning
confidence: 99%
“…The data of the present study suggests that the up‐regulation of AT1R in both donor hearts and donor lymphocytes indicates the presence of a generalized activation of the RAS. This concept is supported by experimental models that showed activation of both circulating and central nervous system RAS following subarachnoid hemorrhage (13,18). In conclusion, donor spontaneous intracerebral hemorrhage is associated with up‐regulation of AT1R and subsequent development of transplant coronary vasculopathy.…”
Section: Discussionmentioning
confidence: 77%
“…Both clinical and experimental investigations suggest that the activation of the renin‐angiotensin system (RAS) occurs along with increased sympathetic drive in patients with spontaneous ICH (12). Angiotensin II interacts with the sympathetic nervous system to maintain an adequate cerebral perfusion (13,14). Clinical studies have demonstrated that plasma renin activity may correlate with the size of bleed and prognosis in subjects after subarachnoid hemorrhage (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some animal studies provide supporting evidence for this hypothesis [34,35], although the data are controversial [36,37]. In the authors' large, retrospective study of medication exposures and SAH-associated vasospasm, prior use of ACE inhibitors and ARBs had no effect on the incidence or severity of vasospasm and on clinical outcome [29].…”
Section: Ace Inhibitorsmentioning
confidence: 99%